Plasma amyloid beta biomarkers predict amyloid positivity and longitudinal clinical progression in mild cognitive impairment - Takuya Ataka; Noriyuki Kimura; Naoki Kaneko; Teruaki Masuda; Yosuke Takeuchi; Kenichi Yabuuchi; Takeshi Mizukami; Tsukasa Takeuchi; Temmei Ito; Hideaki Tasai; Takehiko Miyagawa; Shunya Hanai; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Previous studies have examined the predictive accuracy of plasma amyloid beta (Aβ) biomarkers in clinical cohorts. However, their accuracy for predicting amyloid‐positive patients in community‐based cohorts is unclear. This study aimed to determine the predictive accuracy of Aβ precursor protein 669‐711/Aβ1‐42, Aβ1‐40/1‐42 and their composite biomarkers for brain amyloid deposition or the clinical progression in community‐dwelling older adults with mild cognitive impairment (MCI). METHODS This prospective cohort study was conducted from August 2015 to September 2019. Subsequently, the participants underwent follow‐up cognitive assessments up to 8 years after the start of the study. Blood samples were collected from older adults aged ≥ 65 years with MCI at baseline. Plasma Aβ biomarkers were analyzed using immunoprecipitation‐mass spectrometry. The accuracy of plasma biomarkers for brain amyloid status was evaluated using receiver operating characteristic curve analysis. Relationships between comorbidities and plasma Aβ markers were examined using multiple linear regression analysis. Associations of plasma biomarkers with clinical conversion to Alzheimer's disease (AD) dementia were evaluated using Kaplan‒Meier curves. RESULTS The participants included 107 patients (57 [53.3%] females, median age: 76.0 [72.0–80.0] years). Plasma biomarkers correlated with cortical amyloid uptake (ρ = 0.667–0.754). The composite biomarker had the best area under the curve (0.943, 95% confidence interval [CI]: 0.901 to 0.985) for predicting amyloid positivity. Apolipoprotein ε4 status showed significant correlations with increased plasma amyloid biomarker levels. Participants with high composite biomarker levels at baseline had a greater risk of conversion to AD dementia (hazard ratio 10.74, 95% CI: 3.51 to 32.84, P < 0.001). The higher composite biomarker was associated with a faster rate of cognitive decline (ρ = −0.575, P < 0.001). DISCUSSION Plasma Aβ composite biomarker may serve as a surrogate measure for amyloid deposition and a predictor of disease progression in a community‐based cohort. Highlights Plasma amyloid beta (Aβ) biomarkers correlated with 11C‐Pittsburgh compound B uptake, mainly in the frontal/parietotemporal cortices and posterior cingulate gyrus. The amyloid composite biomarker can predict amyloid positron emission tomography positivity with a high area under the curve of 0.943 in a community‐based mild cognitive impairment cohort. The higher amyloid composite biomarker at baseline was significantly associated with worsening Mini‐Mental State Examination score and a high risk for developing Alzheimer's disease (AD) dementia over 8 years. The amyloid composite biomarker can predict clinical progression to AD dementia with a high area under the curve of 0.860. Apolipoprotein E ε4 status influenced the plasma Aβ biomarker levels.